Regional Development Strategy in the South Cross Road Network of Cilacap - Muhammad Husnul Maab (JUSS (Jurnal Sosial Soedirman), 2023)
The national development of “Jaringan Jalan Lintas Selatan” on the West Java’s Boundary -Patimuan-Bantarsari is one of the opportunities for the Cilacap Regency to develop regional development. It is necessary to combine development planning in sectoral and regional policies. Using the kernel density estimation method, an estimate of the density function in the research area is obtained, including land capability, distribution of facilities, superior potential, and the level of regional accessibility. By combining with various spatial documents and development plans, the research results obtained in the form of regional development strategies around the “Jaringan Jalan Lintas Selatan” based on the local economy through agricultural activities, fisheries, and Micro, Small, and Medium Enterprises. As for what is still a problem in regional development are the problem of regional accessibility and the need to fulfill public health facilities.